2018
DOI: 10.1111/cdev.13025
|View full text |Cite
|
Sign up to set email alerts
|

Development of Social Working Memory in Preschoolers and Its Relation to Theory of Mind

Abstract: Social working memory (WM) has distinct neural substrates from canonical cognitive WM (e.g., color). However, no study, to the best of our knowledge, has yet explored how social WM develops. The current study explored the development of social WM capacity and its relation to theory of mind (ToM). Experiment 1 had sixty-four 3- to 6-year-olds memorize 1-5 biological motion stimuli, the processing of which is considered a hallmark of social cognition. The social WM capacity steadily increased between 3- and 6-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 67 publications
(182 reference statements)
1
35
1
Order By: Relevance
“…Since the BM-WM buffer is suggested to play an important role in transferring ongoing social information from perception to WM (Urgolites and Wood, 2013; Shen et al, 2014), it is possible that the BM-WM capacity could inherently predict one’s social ability instead of the general cognitive ability (e.g., Gf). Corroborating this possibility, we recently found that BM-WM capacity positively correlated with both empathy (Gao et al, 2016) and theory of mind score (He et al, 2019), whereas such a relation vanished for WM capacity of movements of rectangles (i.e., non-animate motion) or of colors (i.e., object-WM). Because of the intimate relation between BM and social ability in both perception and WM, it has been suggested that BM-WM is a representative of social WM (He et al, 2019), which maintains and manipulates a limited set of social information in an online manner and is of paramount importance for navigating our social environment (Meyer and Lieberman, 2012), and is the best manner to measure the development of social WM in preschoolers (He et al, 2019).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Since the BM-WM buffer is suggested to play an important role in transferring ongoing social information from perception to WM (Urgolites and Wood, 2013; Shen et al, 2014), it is possible that the BM-WM capacity could inherently predict one’s social ability instead of the general cognitive ability (e.g., Gf). Corroborating this possibility, we recently found that BM-WM capacity positively correlated with both empathy (Gao et al, 2016) and theory of mind score (He et al, 2019), whereas such a relation vanished for WM capacity of movements of rectangles (i.e., non-animate motion) or of colors (i.e., object-WM). Because of the intimate relation between BM and social ability in both perception and WM, it has been suggested that BM-WM is a representative of social WM (He et al, 2019), which maintains and manipulates a limited set of social information in an online manner and is of paramount importance for navigating our social environment (Meyer and Lieberman, 2012), and is the best manner to measure the development of social WM in preschoolers (He et al, 2019).…”
Section: Introductionmentioning
confidence: 91%
“…1 Later neuroimaging studies further uncovered the neural substrates of BM-WM by showing that the mirror neuron system (MNS) plays a pivotal role in retaining BM in WM (Gao et al, 2013; Lu et al, 2016; Cai et al, 2018). Recent studies have also begun to explore issues such as the development of BM-WM (He et al, 2019), the influence of other social information (e.g., social interaction and emotion) on BM-WM capacity (Ding et al, 2017; Guo et al, 2019), BM-related binding in WM (Wood, 2008; Poom, 2012; Ding et al, 2015; Gu et al, 2019), the representation format of BM in WM (Vicary and Stevens, 2014; Vicary et al, 2014), and the frame of reference for remembering BM (Wood, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Biological movements are one of the most complex stimuli in our daily life, and contain rich social information. The study revealed that VWM capacity for biological movements not only predicts core social ability (Gao et al, 2016 ; He et al, 2019 ), but also predicts canonical cognitive ability (e.g., fluid intelligence).…”
mentioning
confidence: 94%
“…Three‐month‐old infants can discriminate the pattern of human gait present in PLD (Booth, Pinto, & Bertenthal, ) whereas 4‐month olds have exhibited a preference for a canonical BM over an inverted BM (Fox & McDaniel, ) and 5‐month olds can discriminate BM from similar moving dots with perturbed local rigidity (Bertenthal, Proffitt, & Kramer, ) and detect walking direction in PLDs (Kuhlmeier, Troje, & Lee, ). Children at age of three can readily recognize monadic BM (Mitkin & Pavlova, ) and hold at least one BM stimulus in working memory (He, Guo, Zhai, Shen, & Gao, ). However, the vast majority of developmental work on BM perception still focuses on monadic BM perception whereas little research concerns communicative acts between people in interactive BM, which are certainly required in social interactions (Manera et al, ; Manera, von der Luhe, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that intention inference (e.g., theory of mind, emotion understanding), which rapidly develops during preschool stage, has immense value for young children's effective social adaptation (Denham et al, ; Devine, White, Ensor, & Hughes, ; Peterson & Siegal, ; Slaughter, Dennis, & Pritchard, ). Relevant developmental research focused on action perception involved in monadic PLD BM or real‐world contexts has found that better perception of human BM predicts higher social cognitive ability (e.g., theory of mind; Burnside, Wright, & Poulin‐Dubois, ; He et al, ; Rice, Anderson, Velnoskey, Thompson, & Redcay, ) and superior social competence (e.g., larger social network, better peer cooperation; Endedijk, Meyer, Bekkering, Cillessen, & Hunnius, ; Kirby, Moraczewski, Warnell, Velnoskey, & Redcay, ; Krogh‐Jespersen, Liberman, & Woodward, ). However, despite the ability to perceive the actions of others, precisely interpreting underlying shared intentions and interpersonal relationships in peer interactions may be more important if a child wants to have effective social interactions and to be well accepted.…”
Section: Introductionmentioning
confidence: 99%